The properties of recycled precast concrete hollow core slabs for use as replacement aggregate in concrete - Marmash, Basem Ezzat (2011)
The dumping cost of wasted concrete including the rejected units in precast concrete plants is expected to keep rising as the production increases. The waste material from precast concrete hollow core floors (hcu) is high grade and uncontaminated material. This research work was carried out to investigate mainly the strength and other engineering properties of high strength concrete made with recycled concrete aggregate derived from rejected hcu. Three major categories (based on a questionnaire) were investigated: (i) Type of crushers and the crushing method, (ii) The properties of RCA output from these crushers, (iii) The performance of fresh and hardened concrete, including prestressed concrete, with these RCA.